PENGARUH ESG DISCLOSURE, GREEN ACCOUNTING DAN INTELLECTUAL CAPITAL TERHADAP FIRM VALUE : THE EFFECT OF ESG DISCLOSURE, GREEN ACCOUNTING AND INTELLECTUAL CAPITAL ON FIRM VALUE - Prasetiyo, Rendy; Annisa, Dea (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) Disclosure, Green Accounting, and Intellectual Capital on Firm Value among Indonesian listed companies. Using a quantitative associative approach, this study employs panel data regression on a purposively selected sample of 17 companies listed in the Indonesia Stock Exchange ESG assessment during             2021–2023. Secondary data were analyzed using EViews 13. The empirical results indicate that ESG Disclosure and Intellectual Capital have no significant effect on Firm Value, whereas Green Accounting has a negative and significant influence. These findings suggest that investors value firms’ environmental performance more than social, governance, or intellectual factors. Strengthening green accounting implementation can enhance firm reputation, sustainability, and market value.